Contrasting exhumation histories along a crustal-scale strike-slip fault zone: The Eocene to Miocene Ailao Shan-Red River shear zone in southeastern Tibet. (15th December 2015) - Chen, Xiaoyu; Liu, Junlai; Tang, Yuan; Song, Zhijie; Cao, Shuyun
Highlights: The ALS massif experienced generally diachronous cooling histories. An early fast and a late slow cooling characterize the exhumation of the ALS massif. We show the contrast cooling histories of massifs along the same shear zone. Tectono-magmatic activities contribute to the contrasting cooling/exhumations of the massifs. Abstract: Four metamorphic massifs in southeastern Tibet – the Xuelong Shan (XLS), Diancang Shan (DCS), Ailao Shan (ALS) and Day Nui Con Voi (DNCV) – have been suggested to constitute coherent parts of the Ailao Shan-Red River (ASRR) shear zone. This study details the cooling/exhumation histories of the crustal-scale shear zone by determining the cooling paths of the ALS massif and comparing these paths to those of the DCS massif. We show that the different parts of the ALS massif have experienced two stages of diachronous cooling histories. The two cooling stages of the ALS massif, i.e., an early rapid cooling of ca. 45–715 °C/Myr and a late slow cooling of 10–17 °C/Myr, differ significantly from the cooling of the DCS massif along the same shear zone, which featured an early slow cooling of 11–17 °C/Myr and a late rapid cooling of 30–140 °C/Myr. This study confirms that differing cooling/exhumation histories exist along the same crustal-scale shear zone. From the contrasting cooling/exhumation histories, we would argue that the ALS and DCS massifs are isolated units with different tectono-thermal histories during the Oligo-Miocene tectonic evolution of southeastern Tibet.